Developing programmes for violent offenders - Howells, Kevin (Legal and criminological psychology, 1997)
Purpose. The objectives of this paper are to review issues arising in the development of intervention and rehabilitative programmes for violent offenders. The scope of the paper is mainly restricted to programmes within prison and correctional settings. Argument. Relevant literature relating to the development of programmes for violent offenders is reviewed. We argue that a number of preconditions exist for well-founded programmes. These include an adequate theoretical basis, individual formulation, population needs analysis, breadth of approach, cultural relevance, systemic integration, targeting of programmes and evaluation of outcomes. Conclusions. We conclude that addressing these issues is likely to lead to improved effectiveness in violence prevention.